A atuação profissional da assistente social na execução da medida socioeducativa de internação masculina no estado de Sergipe - Góis, Marirose Vilanova de (2015)
The present study analyzes the professional practice of social workers inserted in the execution of male hospitalization measure in the state of Sergipe. In this sense the methodological procedures adopted were guided by critical-dialectical approach, because we believe that this allows us to grasp the object in a whole perspective, we want it, from this, an analysis that goes beyond the appearance of phenomena. As data instrument used the form applied by the researcher in direct contact with the research subjects, social workers who work or have worked with execution of male hospitalization socio-educational measures in the state of Sergipe. Systematized in three chapters, holds in its Chapter I, introductory reflections on the foundations of social policy in capitalist society, and particurlamente in Brazil, with the child's care of the construction process and adolescents in Brazil, culminating with the presentation of barriers will materialization legal and theoretical assumptions specific to this age group. Already the Chapter II, places the insertion of Social Work in the context of the implementation of educational measures, to then introduce the institution responsible for this execution in the state of Sergipe. We continue presenting the profile of professionals who work with the implementation of socio-educational measures of male hospital in the state of Sergipe, as well as the profile of adolescents in compliance with socio-educational measures internment men during the year 2014. In its Chapter III, performs professional performance analysis to properly presenting the characterization of professional practice in the implementation of socio hospitalization measure, the professional activities carried out by social workers, the main tools and techniques used during this operation, the legal parameters used during professional performance, with emphasis on analysis about SINASE, the gaps in professional practice and finally the positive factors / facilitators and negative / hindering of professional practice in the implementation of socio-educational internment measure in the state of Sergipe.